234k views
15 votes
Expand (10-2q) (10+2q)​

User Engam
by
6.0k points

2 Answers

6 votes

Answer:


100-4q^(2)

Explanation:


\\(10-2q)(10+2q)\\=(10)(10)+10(2q)-2q(10)-(2q)^(2) \\=100+20q-20q-4q^(2) \\=100-4q^(2)

User Sonu Jha
by
5.9k points
10 votes

Answer:

100 - 4q²

Explanation:

(10 - 2q)(10 + 2q)

each term in the second factor is multiplied by each term in the first factor.

10(10 + 2q) - 2q(10 + 2q) ← distribute parenthesis

= 100 + 20q - 20q - 4q² ← collect like terms

= 100 - 4q²

User Simon Temlett
by
6.0k points